The Contribution of Ultrasonographic Characteristics of Mediastinal Lymph Nodes on Differential Diagnosis of Tuberculous Lymphadenitis from Sarcoidosis - Erol, Serhat (Tanaffos, 2018)
BACKGROUND: Sarcoidosis and Mediastinal Tuberculous Lymphadenitis (MTLA) are two granulomatous diseases. Differentiation between these two diseases is dependent on clinical presentation, microbiological investigation, and cytopathological examination. In endemic regions, differential diagnosis of MTLA and sarcoidosis might be difficult. Endobronchial ultrasound guided Transbronchial Needle Aspiration (EBUS-TBNA) is a new diagnostic procedure for the diagnosis of mediastinal lymphadenopathy. EBUS not only enables the sampling of Lymph Nodes (LN), but also visualization of sonographic features of them. We hypothesized that the sonographic features of LN may help to differentiate MTLA from sarcoidosis. MATERIALS AND METHODS: This is a retrospective analysis of patients with intrathoracic lymphadenopathy who underwent EBUS-TBNA and were finally diagnosed as sarcoidosis or MTLA. Size, shape, margin, echogenicity, and coagulation necrosis were compared between the groups. RESULTS: A total of 257 LNs (215 sarcoidosis, 42 MTLA) were examined in 101 patients. A heterogeneous echotexture of lymph nodes was significantly more common (P <0.0001) in MTLA (69%) than sarcoidosis (36.2%). Also, necrosis was statistically significantly higher in MTLA compared to sarcoidosis (P<0.0001). The vascular pattern was similar in both groups (P=0.9050). Nearly half of the patients had grade 1 vascular pattern in both groups. The odds for diagnosis of MTLA were significantly higher in the presence of heterogeneous echotexture (odds ratio [OR], 7,00) or necrosis sign (OR, 131,2). CONCLUSION: Vascular patterns of two diseases were similar. Heterogeneous echotexture and necrosis sign in the LNs on EBUS are specific for MTLA. Combination of these findings with a positive tuberculin skin test, favors the diagnosis of MTLA over sarcoidosis.